PENGARUH MINUMAN BEROKSIGEN TERHADAP SISTEM IMUN, KADAR MALONALDEHIDA DAN PERFORMA RESPONDEN MAHASISWA OLAHRAGAWAN [Effect of Oxygenated Water on Immune System, Malonaldehyde Content and Student-Athlete Performance] - Cesar Welya Refdi; Fransiska Rungkat Zakaria; Puspo Edi Giriwono (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2014)
PENGARUH MINUMAN BEROKSIGEN TERHADAP SISTEM IMUN, KADAR MALONALDEHIDA DAN PERFORMA RESPONDEN MAHASISWA OLAHRAGAWAN[Effect of Oxygenated Water on Immune System, Malonaldehyde Content and Student-Athlete Performance]Cesar Welya Refdi, Fransiska Rungkat Zakaria* dan Puspo Edi GiriwonoDepartemen Ilmu dan Teknologi Pangan, Fakultas Teknologi Pertanian, Institut Pertanian Bogor, Bogor Diterima 23 Agustus 2013 / Disetujui 01 Juli 2014ABSTRACT Exercise requires more oxygen input and cannot be fully obtained through breathing. The body has a homeostatic system, when more ATP is needed, the more oxygen is required by the body. Limited supply of oxygen such as those happens in athlete’s body automatically switches the respiration from aerobic into anaerobic. This situation results in building up of lactic acid which in turn lowers the energy for cellular metabolism as well asenergy for exercise. The purpose of this study was to assess the effects of short-term and long-term drinking of oxygenated water on lactic acid and energy expenditure (EE) in exercise performance; Cluster of Differentiation-4 (CD4), CD8, CD56, Interleukin-6 (IL-6) contents; and level of malonaldehyde. During short-term intervention, 12 male student volunteers drank oxygenated (50, 80 and 130 ppm) water and normal mineral water, 15 minutes before treadmill and after treadmill (10 Kmh). The lactic acid concentration was measured before and after treadmill, and 5 minutes after the reconsumption of the oxygenated water. During long-term intervention, 17 male student volunteers drank oxygenated (100 ppm) water twice a day for 21 days. The blood plasma and lymphocyte sampled before and after intervention were analyzed for the same parameters. The results showed that oxygenated water had no effect on lactic acid accumulations and EE. Similarlyt he long-term study showed that oxygenated water did not affect CD4 and CD8, had no harmful effect on IL-6 and malonaldehyde, yet it significantly increased the CD56 content.